1997
DOI: 10.1007/s002619900257
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian fibroma: findings by contrast-enhanced MRI

Abstract: Ovarian fibromas are solid neoplasms that are difficult to differentiate radiologically from uterine leiomyomas. In this report, we describe the contrast-enhanced magnetic resonance imaging features of a 13-cm-diameter solid pelvic mass that allowed us to make the prospective diagnosis of ovarian fibroma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 8 publications
2
9
0
Order By: Relevance
“…Fourthly, supplementary computerized tomography and magnetic resonance imaging may help to improve the diagnostic accuracy. Most ovarian fi bromas appear as a solid mass with delayed accumulation of contrast medium on computerized tomography scan and show marked T 1 and T 2 hypointensities on magnetic resonance imaging [12,13] . Although the ultimate diagnosis depends on the intraoperative fi ndings and should be confi rmed histologically, yet a good preoperative assessment is important for treatment planning and patient counseling.…”
Section: Discussionmentioning
confidence: 99%
“…Fourthly, supplementary computerized tomography and magnetic resonance imaging may help to improve the diagnostic accuracy. Most ovarian fi bromas appear as a solid mass with delayed accumulation of contrast medium on computerized tomography scan and show marked T 1 and T 2 hypointensities on magnetic resonance imaging [12,13] . Although the ultimate diagnosis depends on the intraoperative fi ndings and should be confi rmed histologically, yet a good preoperative assessment is important for treatment planning and patient counseling.…”
Section: Discussionmentioning
confidence: 99%
“…We consider that the areas of low signal intensity on both T1-and T2-weighted images should suggest the diagnosis of probable ovarian fibroma or thecoma [9].…”
Section: Discussionmentioning
confidence: 99%
“…They represent approximately 4 % of all ovarian tumors and are often associated with ascites or torsion [9]. It has been reported that ovarian fibromas have low signal intensity on both T1-and T2-weighted MR images [7,8,9,10,11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian fibromas are well circumscribed solid tumours which demonstrate low signal intensity on both T1- and T2-weighted images, not unlike leiomyomas. Fibromas show minimal enhancement [36,37] . The multi-planar imaging allows differentiation of an ovarian fibroma from an exophytic leiomyoma or other tumours [20,21] .…”
Section: Diagnosis/characterisation Of Pelvic Massesmentioning
confidence: 99%